Virological and immunological impact of integrase inhibitor-based regimens initiated during primary HIV-1 infection. (15th March 2020) - Veil, Raphael; Poizot-Martin, Isabelle; Reynes, Jacques; Goujard, Cecile; Seng, Remonie; Delobel, Pierre; Cotte, Laurent; Duvivier, Claudine; Rey, David; Tran, Laurent; Surgers, Laure; Allavena, Clotilde; et al.
Abstract : Design: Current international guidelines recommend either boosted protease inhibitor (PI/r)-based or integrase inhibitors (INSTI)-based regimens during primary HIV infection (PHI), even though the latter have only demonstrated their superiority at the chronic stage. We compared the effectiveness of INSTI-based versus PI/r-based combined antiretroviral therapy (cART) initiated during PHI. Methods: This study was conducted among patients who initiated cART between 2013 and 2017, using data from the ANRS-PRIMO cohort and the Dat'AIDS study. Cumulative proportions of patients reaching viral suppression (HIV-1 RNA <50 copies/ml) were calculated using Turnbull's estimator for interval-censored data. CD4 + cells and CD4 + /CD8 + ratio increases were estimated using mixed linear models. Results were adjusted for the data source. Results: Among the 712 study patients, 299 received an INSTI-based cART. Patients' baseline characteristics were similar between groups. Viral suppression was reached more rapidly in INSTI-treated versus PI/r-treated patients ( P < 0.01), with cumulative proportions of 32 versus 6% at 4 weeks, 72 versus 31% at 12 weeks, 91 versus 78% at 24 weeks and about 95% in both groups at 48 weeks. At 4 weeks, INSTI-treated patients had gained on average 40 CD4 + cells/μl ( P = 0.05) over PI/r-treated ones; mean CD4 + counts were similar in the two groups at 48 weeks. The CD4 + /CD8 + ratio followed the same pattern. Results were similar when restricted to a comparison between dolutegravir-based versus darunavir-based cART. Conclusion: On the basis of this study and available literature, we recommend the use of INSTI-based cART for treatment initiation during PHI, as it leads to faster viral suppression and immune restoration. Abstract : Supplemental Digital Content is available in the text